Making sense of circular economy: Understanding the progression from idea to action - Fenna Blomsma; Mike Tennant; Ritsuko Ozaki (Business Strategy and the Environment, 2022)
This study examines how management and organisation sciences can contribute to and accelerate circular economy (CE) practices by providing insight into how circular oriented innovation (COI) processes unfold. Emergent theory and recent empirical evidence shows that research into CE needs to acknowledge both salient commonalities between circular solutions, but—crucially—also their differences. A range of well-known circular strategy frameworks exist that offer suggestions for understanding circular strategies in relation to each other. However, at present such frameworks tend to be normative and conceptual. Our objective is therefore twofold: (1) to develop an analytical framework for CE that is grounded in both theory and practice, as well as (2) to demonstrate the application of such a framework to a wide range of different circular solutions and how this can lead to new insights and new directions for research. We deploy a longitudinal qualitative multi-case case study design, where we focus on business-led COI projects, covering innovation projects of 23 product(s) (groups) for 19 focal companies. We identify circular pivots, minimal viable circular configuration, continuous improvement of circular configurations and interactions between circular strategies as particularly important phenomena and the importance of taking a longer time horizon to understand circular phenomena in business. Moreover, we identify a lack of application of structured approaches in practice—to complexity, to circular strategies and to value network development—which, if left unaddressed, pose a risk that CE will not achieve a positive systemic impact.
Keywords: 330; circular configurations; circular oriented innovation; circularity Compass; closed-loop; framing; fuzzy solutions; meaning work; multi-flow metabolism; sensemaking; uncertainty